Appunti sull’esclusione sociale nella disabilità - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2019)
The article addresses the issue of social exclusion in disability as an essential exclusion from many interpersonal relationships in everyday life. Starting from an attempt to understand the normal disturbance reaction in the face of otherness, a space is given to the explanation of the affective mechanisms in the mind of the excluded subject and to the experience of those excluded. The article then carries out further pedagogical considerations of opposition to the diffusion of the narcissistic and paranoid traits of the personality at work in our society, as one of the fundamental reasons underlying the exclusion.